HOW TAXPAYER AWARENESS, TAXPAYER KNOWLEDGE, TAX SANCTIONS, TAX SERVICE QUALITY AFFECT ON MOTOR VEHICLES TAXPAYER COMPLIANCE IN BANDUNG CITY - Rustandi, Rustandi; Kurnia, Ia (2020)
The purpose of this study is to assess tax revenue awareness, tax enforcement knowledge, tax penalties, tax service to taxpayers' compliance in compliance with motor vehicle taxes that are available in Bandung city. The study was conducted by taking a sample of 50 respondents by using methods of sampling samples. Data collection was made through questionnaires and observation. Technical data analysis used in this research is linear regression. Based on analysis, it may be known that the taxpayers' consciousness, the knowledge of tax payers, tax penalties, tax compliance of the tax payers in the areas of Bandung city still likely to be small or, it could be said, that public awareness of motor-vehicle taxpayers is still largely a derobligation.